anonymous
  • anonymous
SHOWYOURWORK! (2x^2)(-8x^3) and solve the system of equations 2x-y=-10 3x+4y=1
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
.Sam.
  • .Sam.
There's 2 questions there?
.Sam.
  • .Sam.
(2x^(2))(-8x^(3)) Multiply 2x^(2) by -8x^(3) to get -16x^(5). -16x^(5)
anonymous
  • anonymous
and then solve the two last eqautions

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

.Sam.
  • .Sam.
2x-y=-10..................(1) 3x+4y=1 ...............(2) From 2x-y=-10, 2x=y-10 x=(y-10)/2 ------------------------ From (2), 3x+4y=1 3(y-10)/2+4y=1 Multiply each term by a factor of 1 that will equate all the denominators. In this case, all terms need a denominator of 2. (3(y-10))/(2)+4y*(2)/(2)=1 Multiply 4y by 2 to get 8y. (3(y-10))/(2)+(8y)/(2)=1 The numerators of expressions that have equal denominators can be combined. In this case, (3(y-10))/(2) and ((8y))/(2) have the same denominator of 2, so the numerators can be combined. (3(y-10)+(8y))/(2)=1 Combine all similar expressions in the polynomial. (11y-30)/(2)=1 Multiply each term in the equation by 2. 11y-30=2 move all terms not containing y to the righthand side of the equation. 11y=32 Divide each term in the equation by 11. y=32/11 ------------------------------------------------- x=(y-10)/2 x=((32/11)-10)/2 y=-(39)/(11)
.Sam.
  • .Sam.
x=-(39)/(11) , not y

Looking for something else?

Not the answer you are looking for? Search for more explanations.